2013
DOI: 10.7552/0-1-102
|View full text |Cite
|
Sign up to set email alerts
|

Not Confucius, nor Kung Fu: Economy and Business as Chinese Soft Power in Africa

Abstract: The Chinese presence in Africa is a fact that cannot be ignored by anybody interested in China, Africa or in international affairs in general. Various explanations are given for the source of China's success on the continent. Pang (2009) emphasises Chinese foreign policy: its engagement in the Non-Aligned Movement and the Chinese doctrine of international relations -the so-called Beijing consensus as the main reason why many African governments have decided to tighten their relations with China.Some others, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The Asian powerhouse is able to make inroads into Africa because, unlike the Western world, the Chinese do not 'moralize'. They are not engaged in moral preachings about democracy and human rights (Jara and Kaluzynska 2013). In exchange for access to African resources, they offer assistance in building infrastructure.…”
Section: China's Cultural Exports and Political Valuesmentioning
confidence: 99%
“…The Asian powerhouse is able to make inroads into Africa because, unlike the Western world, the Chinese do not 'moralize'. They are not engaged in moral preachings about democracy and human rights (Jara and Kaluzynska 2013). In exchange for access to African resources, they offer assistance in building infrastructure.…”
Section: China's Cultural Exports and Political Valuesmentioning
confidence: 99%
“…Knowing the extent and source of China's soft power over Africa gives a clearer picture of the latter's objective for participation, against which the working and impact of the economic engagement should be evaluated. Jura and Kaluzynska (2013) point to economic, business, and development factors as key determinants of soft power.…”
Section: Soft Power and Cultural Synergymentioning
confidence: 99%
“…In particular, nations who desire China"s aid, trade, and recognition are also relatively susceptible to its influence. In addition, a study by Jura and Kaluzynska (2013) found that the image of China as a potential investor was an attractive feature.…”
Section: )mentioning
confidence: 99%